G374(P) Menarche, menstruation and menstrual control in young people with down syndrome. (27th April 2016) - Straw, F; McCall, C
Abstract : It is important that all YP and their families have access to accurate information regarding menstrual management. There is a lack of appropriate and up to date information on menstruation available to support young people (YP) with Down syndrome (DS) and their carers. Published data has shown a large variation in expected age and pattern of menstruation. YP and their carers need clear advice so that there is timely preparation for menarche and awareness of options available for menstrual management. Aims: Ascertain difference in age of menarche, pattern of menstruation, frequency of troublesome menstruation and the use of hormonal methods in a group of YP with DS compared with a group of YP with a learning disability (LD) and other YP. To establish the effectiveness and tolerability of desogestrel in YP. To compare the cost of treatment options for menstrual management. Methods: Literature search on age of menarche and pattern of menstruation in YP with DS and the use of hormonal treatment in menstrual difficulties. Standardised questionnaires were completed on YP seen within the Community Paediatric service either in clinic, via telephone or notes review. Results: There is a large variation in age of onset of menarche and menstrual cycle. Menstruation can affect independence of YP with self-care, their mood and general wellbeing. The frequency of menstrual difficulties confirms the need for discussion about available options for medical management. Co-morbidities are frequently present which affect choice of treatment. Hormonal methods used showed an improvement in cycle control and are generally well tolerated without significant side effects. Conclusion: This study has provided current data on age of menarche, the pattern of menstruation and frequency of menstrual difficulties. YP, parents and carers can be given accurate information on likely age of menarche enabling timely preparation. An informed decision can be made if treatment is needed. Desogestrel is an effective and well tolerated option for menstrual control in YP and requires little monitoring compared with other hormonal treatments. The small size of this study and results indicate the ongoing need to record details around menstruation to inform practice.